Design of Digital Book of Pancasila Education Based on Culturally Responsive Teaching (CRT) Using Flip PDF Professional Software - Ayu Febrianti, Fitri; Rokhmaniyah, Rokhmaniyah; Salimi, Moh. (Multidisciplinar (Montevideo), 2025)
Introduction: The development of digital learning emphasizes the need for culturally relevant and engaging materials. Objective: This study aims to design and evaluate a digital book prototype for Pancasila Education.Methods: A descriptive qualitative method was used, applying the Culturally Responsive Teaching (CRT) approach to create engaging and culturally relevant materials. The digital book prototype was developed with Flip PDF Professional software, chosen for its interactive and user-friendly features.Results: The feasibility of the digital book prototype was evaluated by expert validators specializing in educational media and Pancasila Education content. Key aspects such as readability, interactivity, and curriculum alignment were assessed. The findings confirm that the prototype meets the required standards for effective instructional materials and demonstrates significant potential for enhancing elementary-level Pancasila Education.Conclusions: The study shows that integrating the CRT approach with Flip PDF Professional creates an engaging and culturally relevant digital book. This resource effectively supports better Pancasila Education by enhancing student engagement and cultural connection.